Jilbab: Interaksi antara Ideologi, Aturan Berbusana, dan Konsumerisme - Hendra, Hendra; Aepu, Siti Hajar N.; Kumbayoni, Intan; Anjarsari, Hilda (SIGn Journal of Social Science, 2024)
The jilbab, transcending its status as a symbol of religious observance for Muslim women, is now a complex global phenomenon fraught with contested meanings and practices. This research aims to analyze how contemporary jilbab practices and representations are dynamically negotiated at the crucial intersection of ideological forces (religious and political), the logic of dress semiotics as a sign system, and the penetration of global consumer culture. Using a qualitative approach relying on Barthesian semiotic analysis alongside thematic and content analysis of textual and visual data (literature, media, documentation), this study unpacks the interaction of these three dimensions. Findings indicate that the jilbab functions as a visual text with non-singular meanings; diverse styles communicate different and often ambiguous semiotic significations, which are continuously constructed and contested within the ideological arena through struggles over religious interpretation, identity politics, and feminist discourses. Furthermore, it was found that intensive commodification processes through the fashion industry and media have integrated the jilbab into the logic of consumer culture, creating tensions between values of piety, aesthetic expression, and consumptive desire. It is concluded that a holistic understanding of the contemporary jilbab necessitates an interdisciplinary analysis that moves beyond simplistic dichotomies, recognizing the jilbab as a dynamic site of Muslimah identity negotiation amidst the complex interplay of ideology, the dress sign system, and global market hegemony.